2022
DOI: 10.1088/0256-307x/39/2/020501
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Two Dark Solitons in a Polariton Condensate

Abstract: We theoretically investigate dynamics of two dark solitons in a polariton condensate under nonresonant pumping, based on driven dissipative Gross–Pitaevskii equations coupled to the rate equation. The equation of motion of the relative center position of two-dark soliton is obtained analytically by using the Lagrangian approach. In particular, the analytical expression of the effective potential between two dark solitons is given. The resulting equation of motion captures how the open-dissipative character of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Spinor Bose-Einstein condensates (BECs) have attracted great interests of researchers since their experimental realization on the optically trapped 23 Na Bose condensate. [1][2][3][4][5][6][7] Spinor BECs with freedom of internal spin degrees possess abundant phenomena including magnetic crystallization, spin texture, and fractional vortices, which have no counterpart in magnetically trapped condensates with the spin degree being frozen. [7] Many experimental and theoretical studies on spinor BECs have revealed a variety of interesting phenomena, such as polarto-ferromagnetic phase transitions, quantum knots, condensation of magnon excitations, and various kinds of nonlinear excitations consisting of dark/bright solitons, soliton complexes, rogue waves, and vortices, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spinor Bose-Einstein condensates (BECs) have attracted great interests of researchers since their experimental realization on the optically trapped 23 Na Bose condensate. [1][2][3][4][5][6][7] Spinor BECs with freedom of internal spin degrees possess abundant phenomena including magnetic crystallization, spin texture, and fractional vortices, which have no counterpart in magnetically trapped condensates with the spin degree being frozen. [7] Many experimental and theoretical studies on spinor BECs have revealed a variety of interesting phenomena, such as polarto-ferromagnetic phase transitions, quantum knots, condensation of magnon excitations, and various kinds of nonlinear excitations consisting of dark/bright solitons, soliton complexes, rogue waves, and vortices, etc.…”
mentioning
confidence: 99%
“….) be the complex matrix solutions of Lax pair (2) with 𝑄 = 𝑄[0] and 𝜆(𝑡) = 𝜆𝑗(𝑡), we obtain the following 𝑁 th-step DT for system (1): [30] 𝛹…”
mentioning
confidence: 99%
“…The time evolution of the parameters in Eq. ( 7) can be then obtained via the Euler-Lagrangian equations for the dissipative system [43][44][45][46][47]…”
Section: The Theoretical Model and Lagrangian Approachmentioning
confidence: 99%
“…The key assumption underlying the ansatz ( 7 ) is that the functional forms of the soliton and the impurity-induced function are preserved in the presence of perturbation, whereas the corresponding parameters become slowly time-dependent. The time evolution of the parameters in Equation ( 7 ) can be obtained via the Euler-Lagrangian equations for the dissipative system [ 47 , 48 , 49 , 50 , 51 ] with and , and labels the real part of the expression. In Equation ( 8 ), the Lagrangian is referred to as the average Lagrangian of Equation ( 6 ) with , where the Lagrangian density is given by …”
Section: The Theoretical Model and Lagrangian Approachmentioning
confidence: 99%